1989
DOI: 10.1023/a:1015941412620
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: To probe age-related changes in skin barrier function, transepidermal water loss (TEWL) rates have been measured in "young" (19-42 years) and "old" (69-85 years) subjects. TEWL was determined at ventral forearm skin sites, which had been occluded for 24 hr with polypropylene chambers. Baseline TEWL rates (J infinity), which showed no dependence on age, were measured for each subject before and after the experiment. Following removal of the occlusive chamber, TEWL was monitored continuously from t = 0.5 min unt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
29
1

Year Published

1991
1991
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(30 citation statements)
references
References 12 publications
0
29
1
Order By: Relevance
“…Data analysis also indicates that TEWL is not subjected to greater fluctuations over a lifetime. However, TEWL at the neck significantly increases with age, which is contrary to other studies that showed a decreasing TEWL in nonfacial areas with aging [16,19,20,21]. Further, men between the ages of 50 and 60 years show significantly higher water loss (with the exception of the hand) in comparison to the data of other age groups.…”
Section: Discussioncontrasting
confidence: 94%
“…Data analysis also indicates that TEWL is not subjected to greater fluctuations over a lifetime. However, TEWL at the neck significantly increases with age, which is contrary to other studies that showed a decreasing TEWL in nonfacial areas with aging [16,19,20,21]. Further, men between the ages of 50 and 60 years show significantly higher water loss (with the exception of the hand) in comparison to the data of other age groups.…”
Section: Discussioncontrasting
confidence: 94%
“…How age affects the skin permeability is an area under debate since different studies point in different directions [6,32,33]. We found a significant difference between the accumulated absorption of fentanyl over 48 h in young individuals and in middle-aged individuals as well as between young individuals and older individuals.…”
Section: Discussionmentioning
confidence: 66%
“…No correlation with age was found, but compared to our age groups the study by Meidan and Roper contained only 2 young and 2 elderly skin donors, whereas the majority of the donors (11 individuals) was grouped in the middle-aged group. Roskos and Guy [33] compared the skin barrier function by measurements of transepidermal water loss measured in one body site in young and older individuals and found no relation between the barrier function and the age of the individuals. In 1964, Christophers and Kligman [6] demonstrated an increase in permeability of the hydrophilic fluorescein in cadaver skin from elderly individuals and a decrease in the permeability of testosterone in elderly people in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…We evaluated safety through dermatoscopic inspection, biopsy, and TEWL measurements. Measurements of TEWL are frequently used to evaluate the integrity of the skin barrier26. TEWL measurements may provide a rapid and non-invasive evaluation of skin barrier function before penetration experiments with Franz chambers27.…”
Section: Discussionmentioning
confidence: 99%